Developmental control of noradrenergic system by SLITRK1 and its implications in the pathophysiology of neuropsychiatric disorders - Hatayama, Minoru; Aruga, Jun (Frontiers in Molecular Neuroscience, 2023)
SLITRK1 is a neuronal transmembrane protein with neurite development- and synaptic formation-controlling abilities. Several rare variants of SLITRK1 have been identified and implicated in the pathogenesis of Tourette’s syndrome, trichotillomania, and obsessive-compulsive disorder, which can be collectively referred to as obsessive-compulsive-spectrum disorders. Recent studies have reported a possible association between bipolar disorder and schizophrenia, including a revertant of modern human-specific amino acid residues. Although the mechanisms underlying SLITRK1-associated neuropsychiatric disorders are yet to be fully clarified, rodent studies may provide some noteworthy clues. Slitrk1-deficient mice show neonatal dysregulation of the noradrenergic system, and later, anxiety-like behaviors that can be attenuated by an alpha 2 noradrenergic receptor agonist. The noradrenergic abnormality is characterized by the excessive growth of noradrenergic fibers and increased noradrenaline content in the medial prefrontal cortex, concomitant with enlarged serotonergic varicosities. Slitrk1 has both cell-autonomous and cell-non-autonomous functions in controlling noradrenergic fiber development, and partly alters Sema3a-mediated neurite control. These findings suggest that transiently enhanced noradrenergic signaling during the neonatal stage could cause neuroplasticity associated with neuropsychiatric disorders. Studies adopting noradrenergic signal perturbation via pharmacological or genetic means support this hypothesis. Thus, Slitrk1 is a potential candidate genetic linkage between the neonatal noradrenergic signaling and the pathophysiology of neuropsychiatric disorders involving anxiety-like or depression-like behaviors.